Pendidikan Berbasis Welas Asih dalam Buddhisme Humanistik Fo Guang - Tegar Yusteditera; Situ Asih; Prihadi Dwi Hatmono (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the role of Humanistic Buddhism as practiced by Fo Guang Shan in building compassion-based communities through education in Indonesia. As a contemporary Buddhist movement with global development, Fo Guang Shan emphasizes the integration of values such as compassion, wisdom, and humanity into both formal and non-formal educational practices that are relevant to the social context of modern society. Using a qualitative descriptive approach, this research explores in depth the implementation of Humanistic Buddhist values within educational curricula, learning activities, and various community empowerment programs involving interfaith and intercultural engagement. Data were obtained through analysis of educational activities and social practices conducted by Fo Guang Shan in Indonesia. The findings indicate that education grounded in Humanistic Buddhism contributes significantly to fostering interreligious tolerance, shaping learners’ moral character, and promoting social solidarity within Indonesia’s pluralistic society. Beyond academic aspects, Fo Guang Shan’s educational model also prioritizes the development of empathy, social responsibility, and collective awareness to encourage harmonious coexistence. This study concludes that the educational initiatives undertaken by Fo Guang Shan offer a transformative approach to building an inclusive, compassionate society oriented toward sustainable social engagement.